Geographical analysis of the use of clear water in Industrial activities in Baghdad governorate - Salim Ramadhan, Anwer (Journal of College of Education, 2020)
The current study aims to know the geographical analysis of the use of freshwater in industrial activities in the governorate of Baghdad, based on analysis of the spatial relationship between the production of freshwater in purification stations and utilization of that water for existing industrial projects, as well as industrial production diversity, whether it is a private or public sector taking the water as one of the main production requirements included in the industrial process. As well as identifying the nature of freshwater production and extra consumption of water by industrial projects, deficiency, shortage in freshwater production. The study was implemented with descriptive, analytical, and quantitative approaches based on all the research variables. The most achieved results show that the surplus in all centres is about (32,125) m3/ hr while the total supply amount is (3035) m3/hr, whereas the actual need for projects is about (4575) m3/hr. The actual production of the total industries was (30100) tons of various products. The statistical analysis shows a strong correlation between the surplus and available energy and between the required supply of water with a value of (0.99